I Nebeneinander ohne Konflikte: Die multiprofessionelle Struktur interreligiöser Lehrgemeinschaften (Pedagogical Horizons, 2021)
This article examines two religion teachers’ experiences and perceptions of a Catholic-Islamic interreligious team-teaching setting at an Austrian primary school, which was subsequently reflected upon in a group discussion with an equally interreligious team of researchers from the University of Graz. As evaluation method, Bohnsack’s reconstructive social research is used. The central question is how the two teachers reconstruct their experience of cooperation and role identities. Both are perceptibly influenced by the traditions and concepts of their profession embedded in their respective subjects and the religious community behind them. Although the team aims at a professional teaching community, a binary, exclusionary logic of interaction can be reconstructed. As a result, they operate in a hierarchical pattern of interaction typical of multi-professional teams. The religious difference which is supposed to enrich their mode of teaching introduces a certain structure. Actors who see themselves as professionals set themselves apart from other professionalities, especially when the social and institutional situation is processed in conflicting ways. An orientation towards a common goal of action, as required by a teachers’ cooperation such as this, is only possible if the religious difference is neglected, in which case even contrary ideas of professions are brought together.
Keywords: Christian-Islamic team teaching, multi-professional team, beliefs and ideas of action, Bohnsack’s reconstructive social research, practices of differentiation and subjectivation